Analysis of prevalence and associated biomarkers of sarcopenia in older adults living in rural community in Wuhan, China - Zhou, Yun; Zhang, Kemeng; Zhang, Yanling; He, Ping; Wang, Zhaohui (Frontiers in Endocrinology, 2025)
BackgroundSarcopenia is a disease of loss of muscle mass and decreased skeletal muscle function with impaired ability in the activities of daily life. Exploring potential biomarkers for sarcopenia may lead to early screening and intervention for sarcopenia.This study investigated the prevalence and potential biomarkers of sarcopenia in older adults living in rural community in Wuhan,China.MethodsThis cross-sectional study involved 236 older participants (age ≥65 years) who received a health examination that included body composition and 23 circulating biomarkers. Sarcopenia was defined by the Asian Working Group for Sarcopenia revised in 2019 (AWGS2019). We divided the participants into a non-sarcopenia group and a sarcopenia group. The correlation between biomarkers and sarcopenia was analyzed by independent sample t-test, and then the significant variables of the t-test (p < 0.05) were included in the binary logistic regression model to determine the independent factors associated with sarcopenia.ResultsAmong the 236 participants, 61% were females, with a mean age of 70.6 ± 4.4years. The prevalence of sarcopenia in rural community was 25.4%(men 20.7%, women 28.5%). Analyses were conducted using binary logistic regression, growth differentiation factor 11(GDF11), was an independent risk factor for sarcopenia [Exp (B) 1.031, 95% CI: 1.010-1.052, p = 0.003]. Body mass index(BMI), albumin(ALB), fibroblast growth factor 19(FGF19), and tumour necrosis factor alpha(TNF-α) were independent protective factors for sarcopenia [BMI: Exp (B) 0.007, 95% CI: 0.000-0.244, p = 0.006;ALB: Exp (B) 0.490, 95% CI: 0.281-0.853, p = 0.012; FGF19: Exp(B) 0.804, 95% CI: 0.683-0.946, p = 0.009; TNF-α: Exp (B) 0.379, 95% CI: 0.194-0.742, p = 0.005].ConclusionsAbout a quarter of older adults in rural Chinese communities are at risk of sarcopenia. Lower BMI, lower serum ALB, FGF19, TNF-α, and higher circulating GDF11 are associated with sarcopenia.